2015
DOI: 10.1016/j.cpr.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurostimulation as an intervention for treatment resistant depression: From research on mechanisms towards targeted neurocognitive strategies

Abstract: Despite the fact that several interventions for major depression have proven efficacy, a substantial number of patients are or become treatment resistant to various forms of pharmacotherapy and psychotherapy. Biological interventions that directly target brain activity such as electroconvulsive therapy are used to treat these patients, but some of these interventions are unlikely to be easily accepted because of their more invasive nature or sideeffects. The efficacy of non-invasive neurostimulation with a fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 100 publications
3
61
0
6
Order By: Relevance
“…Moreover, anodal tDCS of the prefrontal cortex has been found to reduce state rumination via a beneficial change in working memory processes (Vanderhasselt et al, 2013b) and also causally reduce other depressive symptoms (e.g., Brunoni et al, 2013a). Most important, tDCS doesn't require anesthesia and is well tolerated, which makes it a technique suitable to be combined with cognitive training (De Raedt et al, 2014). It has also been demonstrated that concurrent neurocognitive training enhances the antidepressant outcome of anodal tDCS of the left dorsolateral prefrontal cortex (DLPFC) (Segrave, Arnold, Hoy, & Fitzgerald, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, anodal tDCS of the prefrontal cortex has been found to reduce state rumination via a beneficial change in working memory processes (Vanderhasselt et al, 2013b) and also causally reduce other depressive symptoms (e.g., Brunoni et al, 2013a). Most important, tDCS doesn't require anesthesia and is well tolerated, which makes it a technique suitable to be combined with cognitive training (De Raedt et al, 2014). It has also been demonstrated that concurrent neurocognitive training enhances the antidepressant outcome of anodal tDCS of the left dorsolateral prefrontal cortex (DLPFC) (Segrave, Arnold, Hoy, & Fitzgerald, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, as observed by Siegle et al (2014), the CCT seemed to be most effective to reduce rumination when patients engaged in the working memory task by exerting cognitive resources at the start of the training (this was measured by pupillary responses to index task-related resource allocation). Furthermore, in a recent review, De Raedt, Vanderhasselt, & Baeken (2014) suggested that deficient prefrontal functioning in currently depressed patients might limit the effects of neurocognitive training. In other words, greater prefrontal engagement would augment the effects of neurocognitive training.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we can distinguish between two different cognitive training procedures that might lead to increased stress resilience. (1) Visuospatial cueing tasks to train attention away from negative towards positive information, influencing the way individuals perceive their environment, which would eventually lead to new corrective experiences with more positive aspects of the situation; and (2) cognitive control training to increase the ability to shift away from negative internal presentations in working memory, which would lead to decreased rumination and facilitate reappraisal of negative to positive expectancies (De Raedt, Vanderhasselt & Baeken, 2015). However, studies have shown that these training procedures might be effective in dysphoric individuals (Wells & Beevers, 2010), but less so in depressed patients (Baert et al, 2010, but see Siegle et al, 2014), possibly because depressed individuals are, given their dysfunctional DLPFC related cognitive abilities, unable to deploy their cognitive resources.…”
Section: Neurognitive Framework Regulation Expectation 28mentioning
confidence: 99%
“…Ces résultats ont stimulé l'envie d'évaluer une telle démarche pour son application dans la remédiation de processus cognitifs jouant un rôle psychopathogène qui a été avéré en psychopathologie [33][34][35][36]. Bien que ces travaux soient encore aujourd'hui à un stade quasiembryonnaire, les premiers résultats s'avèrent particulièrement prometteurs [37][38][39]. Étant donné le faible coût de la tDCS, celle-ci pourrait rapidement renouveler l'exercice de l'intervention sur ces processus psychopathogènes [39].…”
Section: Applications Cliniques En Psychiatrieunclassified
“…Étant donné le faible coût de la tDCS, celle-ci pourrait rapidement renouveler l'exercice de l'intervention sur ces processus psychopathogènes [39]. Enfin, au-delà des implications cliniques possibles de la tDCS, la possibilité de manipuler expérimentalement l'excitabilité neuronale de régions cibles et d'en examiner les effets directs sur l'efficience de processus cognitifs psychopathogènes, devrait permettre, à terme, de dépasser les écueils rencontrés dans les recherches réalisées auparavant, comme l'utilisation de plans de recherche qui ne permettent pas l'inférence de relations causales [37][38][39][40]. ‡…”
Section: Applications Cliniques En Psychiatrieunclassified